2021
DOI: 10.47909/ijsmc.120
|View full text |Cite
|
Sign up to set email alerts
|

Research data management: a bibliometric and altmetric study based on Dimensions

Abstract: Objective. This study aims to analyze the scientific production on research data management indexed in the Dimensions database. Design/Methodology/Approach. Using the term “research data management” in the Dimensions database, 677 articles were retrieved and analyzed employing bibliometric and altmetric indicators. The Altmetrics.com system was used to collect data from alternative virtual sources to measure the online attention received by the retrieved articles. Bibliometric networks from journals bibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…According to the study conducted and data triangulation from research similar to ours, future lines should include access to different platforms (24), the metaverse and its opportunities (25) (26) (27) (28) (29) (30), teaching the proper exploitation of these tools (31) (32) (33) (34) (35), attention to psychosocial factors and social networks (36) (37) (38) (39). Special attention should be paid to therapeutic uses (40) (41) (42), aimed at rehabilitation (43) (44) (45), the appropriate use of data for decision making (46) (47) (48) (49) (50) (51) (52), shared access to groups, communities and individual users for a shared learning experience (53) (54) (55) (56) (57).…”
Section: Discussionmentioning
confidence: 99%
“…According to the study conducted and data triangulation from research similar to ours, future lines should include access to different platforms (24), the metaverse and its opportunities (25) (26) (27) (28) (29) (30), teaching the proper exploitation of these tools (31) (32) (33) (34) (35), attention to psychosocial factors and social networks (36) (37) (38) (39). Special attention should be paid to therapeutic uses (40) (41) (42), aimed at rehabilitation (43) (44) (45), the appropriate use of data for decision making (46) (47) (48) (49) (50) (51) (52), shared access to groups, communities and individual users for a shared learning experience (53) (54) (55) (56) (57).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the research themes related to religion in China and identify which of these are the most relevant in terms of impact and relationship, a bibliometric analysis was developed to evaluate the performance of the field under consideration, as well as the mapping of the main themes, authors and organizations between 2014 and 2023 19,20,21 . For this purpose, a methodology was developed in three stages using VOSviewer software as a central tool, these being: i) data retrieval and processing 22,23,24 ; ii) elaboration and normalization of the scientific maps 25,26,27 ; and iii) visualization and analysis of the main relationships in the research themes 28,29 .…”
Section: Dataset and Methodologymentioning
confidence: 99%
“…Real-time graphics allow students to practice and refine these skills without jeopardizing the lives and well-being of actual patients. 14,15 The importance of using real-time graphics in health education has become increasingly evident in the scientific literature. Numerous studies have shown that these technologies can enhance knowledge and skill acquisition, increase student confidence and satisfaction, and ultimately improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%